Mentoring the Department Chair: Creating a Community of Support - Krista Lussier; Brenda Smith; Shawn Read (Academic Chairpersons Conference Proceedings, 2016)
Learn how an active, cross-campus peer network can support the growth and ongoing development of department chairs by assessing needs, building support structures, and nurturing a supportive learning community.
Keywords: Peer support; professional development; academic leadership development; group mentoring; chair support